Labour Welfare and Social Security - Ravindra, K B (Ushus Journal of Business Management, 2016)
Labour Welfare and Social Security has got great relevance and importance in the Public Sector, Private Sector and Multinational Corporations. Since Independence, India has taken to the path of rapid industrialisation and economic growth. Consequently, this has resulted in the rise of great number of industries, a large workforce and a new industrial society. All these factors have considerable bearing on the growth of the labour welfare movement in the country. The ideal of a Welfare State has added new dimensions to the labour welfare philosophy. Labour Welfare plays a very vital role in the industrial economy of any nation. The industrial progress of any nation largely depends on a satisfied labour force. The schemes of Labour Welfare may be regarded as a wise investment which brings satisfaction to employees in an organisation and paves the way for achievement of organisational goals. In the present era of globalisation, it is very important for organisations to study global trends very carefully before designing Labour Welfare and Social Security strategies for their employees and workers. In the above background, the article provides a brief insight into the various aspects of Labour Welfare and Social Security in India. The article also analyses the emerging trends in Labour Welfare and Social Security in India and concludes by stating that although the Government is taking a lot of initiatives, it is a long and difficult road ahead before we can provide Labour Welfare and Social Security to all the workers in India.